2020
DOI: 10.1038/s41598-020-60313-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-appearance of superconductivity and ferromagnetism in a Ca2RuO4 nanofilm crystal

Abstract: By tuning the physical and chemical pressures of layered perovskite materials we can realize the quantum states of both superconductors and insulators. By reducing the thickness of a layered crystal to a nanometer level, a nanofilm crystal can provide novel quantum states that have not previously been found in bulk crystals. Here we report the realization of high-temperature superconductivity in Ca2RuO4 nanofilm single crystals. Ca2RuO4 thin film with the highest transition temperature Tc (midpoint) of 64 K ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 74 publications
2
15
0
Order By: Relevance
“…Another confirmation of this statement comes from the recent fascinating discovery of high-temperature superconductivity in calcium ruthenate, Ca 2 RuO 4 [8]. The stoichiometric composition of this material in a singlecrystalline form is a Mott insulator, while single crystals with excess oxygen are metallic above 160 K [9].…”
Section: Introductionmentioning
confidence: 92%
“…Another confirmation of this statement comes from the recent fascinating discovery of high-temperature superconductivity in calcium ruthenate, Ca 2 RuO 4 [8]. The stoichiometric composition of this material in a singlecrystalline form is a Mott insulator, while single crystals with excess oxygen are metallic above 160 K [9].…”
Section: Introductionmentioning
confidence: 92%
“…On the experimental side, several studies [128][129][130][131] found doping driven ferromagnetic state in Ca 2 RuO 4 ; interestingly, the recent work has reported also on signatures of superconductivity. 132 In compounds with 90 • bonding geometry, the hopping rules are different and interactions are frustrated; studies of doping effects in such systems may bring some surprises.…”
Section: B 90 • M-o-m Bonding Honeycomb Latticementioning
confidence: 99%
“…Owing to their physical and chemical properties, alkali and alkaline earth ruthenates play an important role in magnetics. With regard to this family of compounds, researchers have previously studied the superconductivity of Sr2RuO4 [1], the ferromagnetic transition in Ca2RuO4 [2], and the anti-ferromagnetic behavior of Na2RuO4 [3]. These compounds form different crystalline lattices as influenced by varying external conditions such as temperature.…”
Section: Introductionmentioning
confidence: 99%